Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - R.4 Factoring Polynomials - R.4 Exercises - Page 44: 68



Work Step by Step

Note that $m^4=(m^2)^2$ and $1296=36^2$. Thus, the given binomial is equivalent to: $=(m^2)^2-36^2$ Factor the binomial using the formula $a^2-b^2=(a+b)(a-b)$ where $a=m^2$ and $b=36$ to obtain: $=(m^2+36)(m^2-36) \\=(m^2+36)(m^2-6^2)$ Use the same formula above to factor the second binomial with $a=m$ and $b=6$ to obtain: $\\=\color{blue}{(m^2+36)(m+6)(m-6)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.